Development of fluorescence-based assays to determine changes in membrane potential and K+ levels in isolated Plasmodium falciparum parasites - Niemand, Jandeli (University of Pretoria, 2024)
Dissertation (MSc (Biochemistry))--University of Pretoria, 2024.